Investigation of important morphological traits and grain yield of lentil under shading and bio-priming - feresteh darabi; Ali Hatami; Mohammad Javad Zarea; Rahim Naseri (پژوهش‌های حبوبات ایران)
Introduction Lentil (Lens culinaris Medic) is a member of the leguminosae (Fabaceae) family and an important pulse crop grown in Iran. Growth of lentil plant is highly sensitive to environmental conditions, especially solar radiation, high temperature and water availability. One of the important reasons for unstable lentil yield is the indeterminate growth habit of lentil plants. Extensive vegetative growth, lodging, pod abortion due to limited light interception in the lower part of the canopy, excessive flower and pod shedding, and competition between pods and vegetative parts for photosynthates are all the consequences of indeterminacy and late maturity. Radiation (sunlight) is one the limiting factors in mixed and agroforestry cultivation systems. Crop yield is a function of radiation intercepted over the growing season, the efficiency of converting the intercepted radiation to biomass and the partitioning efficiency of biomass to seed yield. Therefore, in agroforestry production systems, maximizing the limited solar radiation with improved crop management practices such as seed inoculation with plant growth promoting rizobacteria (PGPR) could lead to yield improvement. Intensive use of chemical fertilizers has produced environmental problems and increased the production costs. The recent economic crisis and environmental problems has raised interest in environmental friendly sustainable agricultural practices, which can reduce input costs. N2-fixing may be important for plant nutrition by increasing nitrogen uptake by the plants, and playing a significant role as plant growth promoting rhizobacteria in the bio-fertilization of crops. Plant growth-promoting rhizohacteria are able exit a beneficial upon plant growth. Nitrogen fixation and P. solubilization production of antibiotic and increased root dry weight are the principal mechanism for the PGPR. A number of different bacteria promote plant growth, including Azospirillum sp., Azospirillum species are plant growth-promotive bacteria whose beneficial effects have been postulated to be partially due to production of phytohormons, including gibberellins.